2005
DOI: 10.1007/s00228-005-0932-7
|View full text |Cite
|
Sign up to set email alerts
|

Dermal absorption of permethrin following topical administration

Abstract: The extent of systemic exposure following external therapeutic administration of permethrin is very low compared with doses used for preclinical toxicity studies, and elimination is virtually complete after 1 week. These data provide the pharmacokinetic basis for the clinical safety of topical permethrin.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
51
0
3

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(55 citation statements)
references
References 10 publications
1
51
0
3
Order By: Relevance
“…This disease is caused by the mite Sarcoptes scabiei, which burrows into the skin and consumes epidermis and sera of the host, resulting in inflammation, allergy-like reactions, and pruritic lesions (4)(5)(6)(7). The currently available treatment options for scabies range from topical scabicides like permethrin, pyrethroids, crotamiton, and lindane to oral medications like antihistamines (8). Benzyl benzoate (BB) is one of the oldest drugs used for the treatment of scabies and is considered as the preferred treatment option for the same (9).…”
Section: Introductionmentioning
confidence: 99%
“…This disease is caused by the mite Sarcoptes scabiei, which burrows into the skin and consumes epidermis and sera of the host, resulting in inflammation, allergy-like reactions, and pruritic lesions (4)(5)(6)(7). The currently available treatment options for scabies range from topical scabicides like permethrin, pyrethroids, crotamiton, and lindane to oral medications like antihistamines (8). Benzyl benzoate (BB) is one of the oldest drugs used for the treatment of scabies and is considered as the preferred treatment option for the same (9).…”
Section: Introductionmentioning
confidence: 99%
“…The SHEDS-Multimedia modeling of permethrin , applied a fractional absorption of permethrin based on the dermal dose-excretion study of Tomalik-Scharte et al (2005). Here we modified our method according to Kissel (2011), who observed that in fluxlimited systems (i.e., dermal studies conducted with high surface loadings) an inverse proportionality between surface loading and fractional absorption may be observed.…”
Section: Dermal Exposurementioning
confidence: 96%
“…Obwohl Pyrethrine und Pyrethroide in dieser Altersgruppe verstärkt transdermal penetrieren, verursachen sie dennoch keine systemischen Wirkspiegel bei großflä-chigem Auftragen [4], weil ihre Abbaurate in der Haut (und ggf. auch in der Leber) hoch genug ist (nachgewiesen am Kaninchen [5]).…”
Section: Allgemeine Pharmakokinetische Eigenschaftenunclassified
“…Oxidation, Hydrolyse, Konjugation) sorgt für eine schnelle Elimination, sodass die HWZ von Permethrin kurz ist.Nach Anwendung vom 0,5% Permethrin am Menschen konnten nach 7 Tagen keine Hauptmetabolite des Wirkstoffs im Urin mehr nachgewiesen werden, unabhängig davon, ob eine Lösung (Präparat gegen Läuse) oder Creme (Präparat gegen Skabies) verwandt wurde[4]. (Fall)berichte zu toxischen Wirkungen.Der Absatz von permethrinhaltigen Prä-paraten liegt nach Extrapolation der bekannten Daten seit Zulassung Mitte der 1980er-Jahre weltweit bei 200-250 Mio.…”
unclassified